Membangun Tembok Perlindungan Hak Asasi Manusia di Era Kejahatan Lintas Negara - Nabila Riani; Andi Aina Ilmih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Transnational crime is increasingly widespread in the era of globalization, presenting new challenges in protecting human rights (HAM). This article discusses the need to build a strong wall of human rights protection to combat transnational crime. Transnational crimes such as human trafficking, drug trafficking and terrorism have grown rapidly in the era of globalization. These crimes not only harm the affected countries, but also threaten the human rights of the victims. Transnational crime presents several challenges in protecting human rights. First, its cross-border nature makes law enforcement complicated. Second, the victims of these crimes are often intimidated and do not have access to justice. Third, the lack of international cooperation in fighting transnational crime. To overcome these challenges, it is necessary to build a strong human rights protection wall. Building a wall to protect human rights is a common task for all countries in the world. With strong cooperation and commitment, we can combat transnational crime and protect the human rights of victims.